Lack of Access to Rifaximin Upon Hospital Discharge Is Frequent and Results in Increased Hospitalizations for Hepatic Encephalopathy. Issue 2 (February 2023) - Stoll, Ann Marie; Guido, Maria; Pence, Alicia; Gentene, Anthony J.
Background: Hepatic encephalopathy (HE) is a complication of cirrhosis. Rifaximin, added to lactulose, effectively maintains remission and reduces hospitalizations from HE compared with lactulose alone. Although the clinical evidence supports the use of rifaximin, concerns remain regarding the financial implications and subsequent impact on medication access and outcomes. Objective: The goal of this study was to determine whether medication access to rifaximin at hospital discharge reduces readmission and office visits related to HE. Methods: A retrospective study was conducted in compliance with local institutional review board including cirrhotic patients discharged with a rifaximin prescription for HE. Patients were stratified into 2 groups: those able to obtain rifaximin and those unable to obtain rifaximin upon discharge. The primary outcome was to evaluate the rate of HE recurrence in each group as defined as a composite of readmission or office visit for acute HE within 12 months of discharge. Results: Access to rifaximin significantly reduced the risk of hospital admission and office visit for acute HE over 12 months. A hospitalization or office visit occurred in 24.5% of patients in the medication access group compared with 50% in the group without medication access. Only 58% of patients had access to rifaximin at discharge. Conclusion and Relevance: Rifaximin use was associated with significantly reduced risk of hospitalization and office visits for HE. At discharge, 42% of patients did not have access to rifaximin regardless of being prescribed the medication, identifying that copay is a significant barrier in allowing patients to have access to rifaximin.